MORPHOLOGICAL RESEARCH ON FREE-RESIDUE OXIDATION PROCESSES IN CASES OF DECIDUAL CELLS OF PLACENTA IN CHORIOAMNIONOTIS AND BASAL DECIDUITIS COMBINED WITH IRON-DEFICIENCY ANEMIA IN THE PREGNANT - Ilika, V. V. (International Journal of Medicine and Medical Research, 2017)
Background. The oxidative modification of proteins is lately pivotal to pathologists and it is a new way of research on different pathological conditions, as well as the diagnostics of inflammation processes in placenta. Objective. The study was aimed at the research of nitro peroxides and establishing the specific features of oxidative modification of proteins in inflammation of placenta with iron deficient anaemia in the pregnant. Methods. Сhemiluminescent and histochemical technique (with bromphenol blue on ‘acidic’ and ‘basic’ proteins according to Mikel Calvo) was applied. Results. The intensity of nitro peroxides glow in chorioamnionitis and basal deciduitis increased in comparison with the samples of physiological and iron deficient anaemia gestation. At the same time in chorioamnionitis the glow intensity is higher than in basal deciduitis. Due to the results of immune histochemical technique held while analysing the samples, together with chorioamnionitis and basal deciduitis the R/B increases and in basal deciduitis the rate, is probably, higher, than in chorioamnionitis. At the same time, the extent of oxidative modification of proteins in cases of inflammation with iron deficient anaemia in the pregnant is on the average higher than with no iron deficient anaemia in the pregnant. Conclusions. High level of nitro peroxides in placentae basal plate in secundines inflammation, the increase in R/B rate, in other words the prevalence of ‘acidic’ proteins over ‘basic’ ones, is evidenced due to the increase of the intensity of oxidative modification processes of proteins in cases of deciduitis.